WAR AS AN EXISTENTIAL CHALLENGE AND ACCELERATOR OF THE POSTHUMANISTIC TURN IN MODERN CULTURE - Maksymiak , Taras (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
Introduction. The contemporary era is defined by events with profound historical impact. The war in Ukraine is a radical challenge, dismantling humanist hierarchies and confronting individuals with ontological nothingness. Philosophy shifts from theory to a vital instrument for navigating moral dilemmas. Aim and tasks. The study analyzes war as a factor that intensifies posthumanist transformations. The tasks are: to explore war as a «limit situation» prompting reassessment of subjectivity; to examine how AI and algorithmic control threaten individual responsibility under information aggression; to identify the specifics of the posthumanist turn as it occurs in real conflict zones rather than in conditions of technological peace; to substantiate information hygiene and network solidarity as practical forms of posthumanist responsibility. Methodology. The framework integrates existential-phenomenological analysis and critical posthumanism to examine war as an event reshaping subjectivity. Hermeneutical methods provide interpretations of responsibility in hybrid information warfare. Comparative analysis contrasts classical humanist models with posthumanist subjectivity. Results. Under conditions of armed conflict, the boundary between the human, her smartphone, and her weapon becomes almost ephemeral — this is the defining feature of the posthumanist transition as accelerated by war. Algorithmic systems and AI pose a threat to the very capacity for free judgment, making information hygiene an existential rather than merely technical practice. Discussion. Unlike Braidotti and Hayles, who theorized posthumanism in conditions of technological stability, Ukrainian wartime experience shows that the posthumanist transition can be forced, rapid, and existentially threatening. The paradox of digital inclusion — simultaneous connection and atomization — is central to this experience. Conclusions. War accelerates posthumanist transition differently from peaceful technological development: the integration is forced, immediate, and bound to existential threat. AI in conditions of information warfare becomes an active agent capable of undermining free judgment, making information hygiene an existential practice. Posthumanism in the context of armed conflict does not mean the abandonment of humanity; rather, the awareness of interdependence that emerges through shared danger becomes the foundation of a new ethics of solidarity and responsibility.